Strategies to Reduce Injuries and Develop Confidence in Elders (STRIDE): A Cluster-Randomized Pragmatic Trial of a Multifactorial Fall Injury Prevention Strategy: Design and Methods. (14th October 2017) - Bhasin, Shalender; Gill, Thomas M; Reuben, David B; Latham, Nancy K; Gurwitz, Jerry H; Dykes, Patricia; McMahon, Siobhan; Storer, Thomas W; Duncan, Pamela W; Ganz, David A; Basaria, Shehzad; Miller, Michael E; et al.
Abstract: Background: Fall injuries are a major cause of morbidity and mortality among older adults. We describe the design of a pragmatic trial to compare the effectiveness of an evidence-based, patient-centered multifactorial fall injury prevention strategy to an enhanced usual care. Methods: Strategies to Reduce Injuries and Develop Confidence in Elders (STRIDE) is a 40-month cluster-randomized, parallel-group, superiority, pragmatic trial being conducted at 86 primary care practices in 10 health care systems across United States. The 86 practices were randomized to intervention or control group using covariate-based constrained randomization, stratified by health care system. Participants are community-living persons, ≥70 years, at increased risk for serious fall injuries. The intervention is a comanagement model in which a nurse Falls Care Manager performs multifactorial risk assessments, develops individualized care plans, which include surveillance, follow-up evaluation, and intervention strategies. Control group receives enhanced usual care, with clinicians and patients receiving evidence-based information on falls prevention. Primary outcome is serious fall injuries, operationalized as those leading to medical attention (nonvertebral fractures, joint dislocation, head injury, lacerations, and other major sequelae). Secondary outcomes include all fall injuries, all falls, and well-being (concern for falling; anxiety and depressive symptoms; physical function and disability). Target sample size was 5, 322 participants to provide 90% power to detect 20% reduction in primary outcome rate relative to control. Results: Trial enrolled 5, 451 subjects in 20 months. Intervention and follow-up are ongoing. Conclusions: The findings of the STRIDE study will have important clinical and policy implications for the prevention of fall injuries in older adults.